2001
DOI: 10.1002/ijc.1554
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of MUC1 reconfigures the binding properties of tumor cells

Abstract: Although it is known that adhesion and antiadhesion are essential to the metastatic spread of tumor cells, little is known about the molecules that regulate these processes. Key words: selectin; metastasis; ICAM-1; pancreatic cancer; colon cancerHuman MUC1 1-4 is a large, type I transmembrane protein normally expressed on the apical surface of ductal epithelia. 5 MUC1 is synthesized as a single polypeptide chain but exists on the cell surface as a heterodimer. Proteolytic cleavage of the full-length protein r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 41 publications
4
69
0
1
Order By: Relevance
“…Studies 2 from our group have shown that similar carbohydrate structures are expressed on both the full-length and CT3 forms (data not shown), although it is not known if the extracellular domains are glycosylated to the same density. Similar to previous studies (2,4), the tandem repeat domain deleted MUC1F(⌬ TR) protein trafficked to the cell surface and was detected as a broad band with an apparent molecular mass of 60 kDa.…”
Section: Transfection Of Cell Lines and Expression Of Muc1 Deletionsupporting
confidence: 84%
See 2 more Smart Citations
“…Studies 2 from our group have shown that similar carbohydrate structures are expressed on both the full-length and CT3 forms (data not shown), although it is not known if the extracellular domains are glycosylated to the same density. Similar to previous studies (2,4), the tandem repeat domain deleted MUC1F(⌬ TR) protein trafficked to the cell surface and was detected as a broad band with an apparent molecular mass of 60 kDa.…”
Section: Transfection Of Cell Lines and Expression Of Muc1 Deletionsupporting
confidence: 84%
“…1A. DNA encoding the FLAG epitope was added to different MUC1 cDNA con- structs, as described previously (4,31). This insertion yields recombinant product with the epitope tag on the extracellular domain of the protein.…”
Section: Transfection Of Cell Lines and Expression Of Muc1 Deletionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Moreover, in vitro studies showed that increasing MUC1 expression results in decreased adhesion between adjacent cells and between cells and extracellular matrix (ECM). [18][19][20] It also results in contraction of collagen type I matrix and altered expression of epithelial cytokeratins. 21 Therefore, the consistent expression of MUC1 in invasive micropapillary carcinoma on the stromafacing rather than the apical surface of the cellsindependent of the location of the tumor-may be responsible at least in part, for the detachment of the cells from the stroma, one of the main entity-defining features of invasive micropapillary carcinoma.…”
Section: Muc1 In Invasive Micropapillary Carcinoma H Nassar Et Almentioning
confidence: 99%
“…The most used and characterized antigens belong to the HER family. Moreover, other targets have been used and well characterized: EpCAM in breast and gastric cancers (Cimino, Halushka et al, 2009;Wenqi, Li et al, 2009), PSMA in prostate cancer (Ikegami, Tadakuma et al, 2005;Ikegami, Yamakami et al, 2006) or MUC1 in colon and prostate cancer (McDermott, Crocker et al, 2001;Papadopoulos, Sivridis et al, 2001). The continuous discovery of new tumor specific and/or tumor overexpressed antigens by many research groups working in this field will enormously contribute to the development of these treatments, by generating a constant increase in the number of potential antibodies.…”
mentioning
confidence: 99%